2017
DOI: 10.1007/s40264-017-0576-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Eslicarbazepine Acetate as Add-On Therapy in Adults with Refractory Focal-Onset Seizures: From Clinical Studies to 6 Years of Post-Marketing Experience

Abstract: IntroductionEslicarbazepine acetate was first approved in the European Union in 2009 as adjunctive therapy in adults with partial-onset seizures with or without secondary generalization.ObjectiveThe objective of this study was to review the safety profile of eslicarbazepine acetate analyzing the data from several clinical studies to 6 years of post-marketing surveillance.MethodsWe used a post-hoc pooled safety analysis of four phase III, double-blind, randomized, placebo-controlled studies (BIA-2093-301, -302,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
8
15
0
Order By: Relevance
“…These possible explanations for the higher rate of hyponatremia in the monotherapy trials than in the adjunctive trials are similar to those identified during postmarketing surveillance of ESL, where most hyponatremia cases were associated with high ESL doses (>1200 mg), dosing errors (eg, no uptitration and not following the administration guidelines), concomitant medications, and/or comorbidities …”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…These possible explanations for the higher rate of hyponatremia in the monotherapy trials than in the adjunctive trials are similar to those identified during postmarketing surveillance of ESL, where most hyponatremia cases were associated with high ESL doses (>1200 mg), dosing errors (eg, no uptitration and not following the administration guidelines), concomitant medications, and/or comorbidities …”
Section: Discussionsupporting
confidence: 53%
“…It is of note that the threshold for clinically significant hyponatremia is not clear-cut, and that different thresholds are used in different settings. For example, publications have defined hyponatremia as [Na + ] <125 mEq/L (in line with this analysis), 27,29 ≤132 mEq/L, 30 ≤134 mEq/L (with severe hyponatremia defined as ≤128 mEq/L), 6,31 <135 mEq/L, 32 and <137 mEq/L. 33 Therefore, comparisons of hyponatremia rates across studies should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Up to 2.6% of patients report ESL related adverse skin reactions. Less than a third stops the medication as a consequence [54]. The lower incidence of skin reactions may be due to the absent toxic epoxide metabolite when compared to CBZ.…”
Section: Eslicarbazepinementioning
confidence: 99%
“…This new antiepileptic has potential uses for the treatment of trigeminal neuralgia and bipolar disorder. Cases of hyponatremia were recorded [91,100,101].…”
Section: Eslicarbazepine Acetatementioning
confidence: 99%